Adherence to the objectives of the Safe Surgery Saves Lives Initiative: perspective of nurses - Larissa de Siqueira Gutierres; José Luís Guedes dos Santos; Sayonara de Fátima Faria Barbosa; Ana Rosete Camargo Maia; Cintia Koerich; Natalia Gonçalves (Universidade de São Paulo, 2019)
ABSTRACT Objective: to measure the adherence to the objectives of the Safe Surgery Saves Lives Initiative in surgical centers from the perspective of nurses. Method: cross-sectional study, developed through an online survey via the Google Forms® platform. The study participants were 220 nurses from surgical centers in different regions of Brazil. The data were collected through a socio-professional characterization form and a questionnaire in which the participants indicated their level of agreement in relation to the fulfillment of the objectives of the Safe Surgery Saves Lives Initiative. Data analysis was performed using descriptive statistics. Results: objective 1, The team will operate on the correct patient at the correct site, presented the highest levels of total agreement (n = 144; 65.5%) and partial agreement (n = 52; 23.6%). Objective 10, Hospitals and the public health systems will establish routine surveillance of surgical capacity, volume and results, obtained the lowest percentages of total (n = 69, 31.4%) and partial agreement (n = 81, 36.8%). Conclusion: adherence to the objectives of the Initiative is adequate, but there are weaknesses, especially in relation to the prevention of never events.